Pemanfaatan Koleksi Referensi di Perpustakaan IAIN Purwokerto - Antasari, Indah Wijaya (Pustakaloka, 2017)
Reference service is necessary especially in research activity which is appropriate with the reference collection charachteristic. Reference collection service in IAIN Purwokerto Library needs a scientific discourse to know the extent of its utilization. So it can be formulated that the problem statement is how the utilization of reference collection in IAIN Purwokerto Library. This research is start from April to August in 2016 for five mounths. The research is using quantitative approach that the presentation is performed in numeral form. Population is determained from the quantity of the reference collection users in one mounth, with 10% of sample. Data collecting technique is using observation, questionnaire, docomentation and interview. The result showed that the interest of the library user to the reference collection is high at 86,79%. The most intresting collection is comperhensive paper materials (43,40%), and there was 41,51% who use the librarian service in using reference collection. Some of library visitor pruposed to increase the number of comperhensive materials collection either english books or arabian books, collection that is relevance with academical needs, and improving the quality of services such as the amiability of the librarian, the arrangement of shelves, and the comfort of the room.